Effect of interference percentage on damage mechanism of carbon fiber reinforced plastics laminate during interference-fit bolt installation. (April 2017) - Song, Danlong; Zhang, Kaifu; Li, Yuan; Liu, Ping; Yan, Xiaoye; Su, Wenlong
The interference-fit joint of composite laminates is widely used in assembly of thin-walled components in aviation product, but the interference percentage has a significant effect on squeezed damage which may reduce structural reliability. An investigation is conducted into the in-plane stress distribution and initial damage mechanism of symmetrical carbon fiber reinforced plastics laminates during the interference-fit bolt installation process. Considering the elastic deformation of the bolt, a general stress distribution model around the interference-fit joint is established with complex potential method. The initial damage mechanism of carbon fiber reinforced plastics laminates is characterized and critical interference percentages without damage are obtained with the mixed damage criteria. The effects of ply orientation and interference percentage on damage mechanism of each individual layer are discussed. Then, extensive finite element models with USDFLD subroutine of interference fit process are used to analyze and simulate the stress distribution and squeezed damage which are validated by strain measurement and micrographs by experiments subsequently. It is observed that theoretical solutions fall within the finite element results. The matrix tensile damage occurs first, and the critical interference percentages decrease from 1.10% to 0.85% with bolt diameters varying from 4 to 10 mm.